Formation Of Readers' Reception in The Process of Studying Modern Foreign Literature - Tugalov Ismat Xatamovich (Genius Journals, 2022)
The article considers the formation of reader's reception in the process of studying modern foreign literature. It is studied how familiarization with foreign fiction contributes to the development of creative thinking of students who understand that artistic consciousness is not standard, that there are different ways of aesthetic exploration of reality.
Keywords: Reader's perception; creative thinking, foreign literature; aesthetic assimilation of reality; method